Free speech : a history from Socrates to social media - Mchangama, Jacob, 1978- (Basic Books, Hachette Book Group, 2022)
"Often hailed as the "first freedom," free speech is the bedrock of democracy, the enemy of tyranny, and the gateway to enlightenment. Research reveals a strong correlation between freedom of speech and democracy, innovation, and advancements in human rights, as well as reductions in conflict, corruption, and discrimination. But for all its benefits, free speech remains a challenging, controversial, and often counterintuitive principle, easily subject to erosion in times of social and political upheaval. And today, in democracies and authoritarian states around the world, freedom of speech is now on the retreat. In Free Speech, Jacob Mchangama traces the long, contested history of a powerful idea, beginning with its origins in the intellectual ferment of classical Athens, where it enabled the development of the world's first democracy. Through captivating stories of defenders of free speech throughout history, from the eighth century 'Abbāsid caliph Abū Ja'far al-Manṣūr to the anti-lynching crusader Ida B. Wells, Mchangama reveals how the free exchange of knowledge and ideas underlies all scientific and literary achievement, and how it has enabled the advancement of civil rights across the globe. Indeed, he argues, freedom of speech has far more often served the cause of the oppressed than the cause of the oppressors. Yet the temptation to restrict speech, too, is a historical constant, and Mchangama explores how elite entrenchment and anxiety about new technologies can lead even the most dedicated defenders of liberty down this dangerous path. Meticulously researched and deeply humane, Free Speech demonstrates just how much humanity has gained from this essential principle - and just how much we stand to lose if we allow it to erode"--